Cricket Steps to Success - Dellor, Ralph (Champaign, Ill. ; Leeds : Human Kinetics, 2010)
This title provides a tried and tested learning formula to help readers master every key skill of cricket. Clear detailed descriptions of techniques are featured along with accompanying photos and diagrams to help readers improve their bowling, batting and fielding.
Includes bibliographical references.
Keywords: Cricket; Sport